Regulation of foliar salicylic acid at the heading stage enhances the grain 2-acetyl-1-pyrroline content and yield in fragrant rice. - Siren Cheng; Xueqing Wang; Likai Zheng; Jinyue Liao; Qingqing Li; Yong Ren (PLoS ONE)
Despite numerous studies on salicylic acid (SA) and its functions, research regarding the regulation of foliar-applied SA at the heading stage in fragrant rice remains scarce. In this study, a pot experiment was conducted using Meixiangzhan and Yuxiangyouzhan cultivars. Exogenous SA was applied at four concentrations, namely 0 (CK), 0.1 mM (SA1), 0.5 mM (SA5), and 1 mM (SA10), during the heading stage to assess its effects on fragrant rice production. The results demonstrated that foliar SA application significantly enhanced the grain 2-acetyl-1-pyrroline (2-AP) content. The SA5 treatment yielded the highest values, with increases of 68.2% and 22.7% for Meixiangzhan and Yuxiangyouzhan, respectively. Moreover, SA application led to improvements in the activity of proline dehydrogenase and the contents of proline, pyrroline-5-carboxylic acid, and pyrroline. Regarding yield, SA application resulted in an increase, with both cultivars achieving a maximum under the SA5 treatment. This was mainly attributed to the enhancement of 1000-grain weight and seed-setting rate, as well as the improved antioxidant properties, particularly the activity of antioxidant enzymes. Principal component analysis revealed distinct differences between the control and treatment groups. Correlation analysis indicated that yield and yield - related traits were both directly and indirectly associated with the 2-AP content, and were regulated by antioxidant oxidase activity and proline content. Overall, the 0.5 mM SA treatment represents an effective strategy for synergistically improving both the yield and aroma of fragrant rice.